A series of novel ferrocenyl derivatives: Schiff bases-like push-pull systems with large third-order optical responses. (February 2017) - Jia, Jianhong; Li, Yizhu; Gao, Jianrong
Abstract: A series of third-order nonlinear optical chromophores containing identical π -bridge and electron-donating groups, but with different electron-withdrawing groups have been designed and synthesized. The ultraviolet absorption, density functional theory calculations, and the third-order nonlinear optical (NLO) properties of these materials have been investigated and systematically studied. A theoretical study showed that the third-order NLO properties were enhanced by the increasing electron-withdrawing ability in accordance with the decreasing energy gap between the highest occupied molecular orbital and the lowest unoccupied molecular orbital. The transferred charge to the substituent is increased and the affect on the electronic reallocation is reinforced with the increasing ability of the compounds to attract electrons. The third-order NLO susceptibilities, the second-order hyperpolarizabilities and response times of compounds were 2.829–6.034 × 10 −13 esu, 0.737–2.005 × 10 −31 esu, 41.92–68.71 fs Our results can be used to develop an efficient design strategy for NLO materials. Graphical abstract: Highlights: A series of ferrocenyl Schiff base derivatives were prepared. The formed chromophores exhibited large third-order nonlinearity. An efficient design strategy for potential nonlinear optical materials is proposed.